Hepatic iron concentration correlates with insulin sensitivity in nonalcoholic fatty liver disease. Issue 6 (27th April 2018) - Britton, Laurence; Bridle, Kim; Reiling, Janske; Santrampurwala, Nishreen; Wockner, Leesa; Ching, Helena; Stuart, Katherine; Subramaniam, V. Nathan; Jeffrey, Gary; St. Pierre, Tim; House, Michael; Gummer, Joel; et al.
Abstract : This randomised controlled trial has studied the effect of venesection on serum adipokine levels in patients with non‐alcoholic fatty liver disease. Venesection did not affect serum adipokine concentrations compared to controls. Hepatic iron concentration however, positively correlated with serum adiponectin and insulin sensitivity index and inversely correlated with multiple markers of insulin resistance. Abstract : Rodent and cell‐culture models support a role for iron‐related adipokine dysregulation and insulin resistance in the pathogenesis of nonalcoholic fatty liver disease (NAFLD); however, substantial human data are lacking. We examined the relationship between measures of iron status, adipokines, and insulin resistance in patients with NAFLD in the presence and absence of venesection. This study forms part of the Impact of Iron on Insulin Resistance and Liver Histology in Nonalcoholic Steatohepatitis (IIRON2) study, a prospective randomized controlled trial of venesection for adults with NAFLD. Paired serum samples at baseline and 6 months (end of treatment) in controls (n = 28) and patients who had venesection (n = 23) were assayed for adiponectin, leptin, resistin, retinol binding protein‐4, tumor necrosis factor α, and interleukin‐6, using a Quantibody, customized, multiplexed enzyme‐linked immunosorbent assay array. Hepatic iron concentration (HIC) was determined using MR FerriScan. Unexpectedly, analysis revealed a significant positive correlation between baseline serum adiponectin concentration and HIC, which strengthened after correction for age, sex, and body mass index (rho = 0.36; P = 0.007). In addition, there were significant inverse correlations between HIC and measures of insulin resistance (adipose tissue insulin resistance (Adipo‐IR), serum insulin, serum glucose, homeostasis model assessment of insulin resistance, hemoglobin A1c, and hepatic steatosis), whereas a positive correlation was noted with the insulin sensitivity index. Changes in serum adipokines over 6 months did not differ between the control and venesection groups. Conclusion: HIC positively correlates with serum adiponectin and insulin sensitivity in patients with NAFLD. Further study is required to establish causality and mechanistic explanations for these associations and their relevance in the pathogenesis of insulin resistance and NAFLD. ( Hepatology Communications 2018;2:644‐653)